Hyperspectral Remote Sensing Applied to Shallow Coastal Waters - Klonowski, Wojciech Mateusz (Curtin University, 2015)
A shallow water reflectance model was developed for application to optical remote sensing in highly diverse and complex coastal environments. A numerical inversion scheme, based on analytical parameterisation, was applied to airborne hyperspectral imagery collected over two regions of the Western Australian coastline; Jurien Bay and the Ningaloo Marine Park. Detailed maps of water quality, water depth and benthic cover classification were derived with a high degree of accuracy as compared to ground truth data.